High Glucose Induces Late Differentiation and Death of Human Oral Keratinocytes - Junhe Shi; Chen Han; Dandan Chen; Harsh M. Trivedi; Hiba I. Bangash; Lin Chen (Current Issues in Molecular Biology, 2022)
Keratinocytes are essential cells for wound repair. Impaired oral wound healing is common in diabetic patients with periodontal disease. High glucose, or hyperglycemia, impairs the cellular function of different cell types. However, it is unknown whether high glucose has a detrimental effect on the functions of oral keratinocytes. In the current study, a human gingival keratinocyte cell line, telomerase immortalized gingival keratinocytes (TIGK), was treated with high glucose (24 and 48 mM) for up to 120 h. Proliferation, migration, cell viability, and production of markers of differentiation, growth factors and enzymatic antioxidants were assessed after high glucose treatment. The results showed that high glucose significantly inhibited TIGK proliferation and migration. High glucose also induced significant cell death through apoptosis and necrosis as determined by flow cytometry, especially at 120 h after high glucose treatment. Necrosis was the dominant form of cell death induced. Real-time PCR showed that high glucose treatment upregulated mRNA expression of late keratinocyte differentiation makers, such as keratin 1, 10, 13 and loricrin, and downregulated enzymatic antioxidants, including superoxide dismutase 1, catalase, nuclear factor erythroid 2 -related factor 2, heme oxygenase 1. In conclusion, high glucose impairs the proliferation and migration of oral keratinocytes and likely induces cell death through the promotion of late cell differentiation and down-regulation of enzymatic antioxidants.